2019
DOI: 10.32394/rpzh.2019.0051
|View full text |Cite
|
Sign up to set email alerts
|

Mineral constituents of conserved white button mushrooms: similarities and differences

Abstract: Background. Mushrooms are a food that is often considered as an important source of minerals and other nutrients for consumers. There is little data on the minerals in mushrooms processed culinary and on the impact of processing. Objective. The research was aimed at understanding the similarities and differences in the mineral composition (Hg, Li, Mg, Al, Co, Ni, Cu, As, Se, Rb, Sr, Ag, Cd, Cs, Sb, Tl, Pb, U, Ba, Cr, Zn, Mn and V) of white button mushrooms (Agaricus bisporus) processed in industrial conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…The Cu concentrations determined in the A. bisporus mushrooms in this study were closer to the lower range of results (mean 36 ± 14 mg kg −1 dw, and total range from 13 to 75 mg kg −1 dw; n = 72 fruit bodies) and 65 ± 9 mg kg −1 dw (n = 15) published for the white strain of button mushroom available from retail outlets in Poland, during 1989-2015, respectively (Falandysz et al 1993Pankavec et al 2019;Rzymski et al 2017), and similarly, for the Australian cultivated white button mushrooms from two producers (range of the means from 35 ± 2 to 61 ± 2 mg kg −1 dw in 6 pools of an unknown number of fruiting bodies) (Koyyalamudi et al 2013). The authors Falandysz et al (1993), Muszyńska et al (2017), Rzymski et al (2017) and Vetter et al (2005) reviewed data on Cu in A. bisporus and presented values in the range from 25 to 125 mg kg −1 dw, from 3 to 65 mg kg −1 dw and from 6.8 to 61 mg kg −1 dw, respectively (no information was provided on the analytical quality of compiled data and sample size information was not included).…”
Section: Copper Manganese and Zincsupporting
confidence: 89%
“…The Cu concentrations determined in the A. bisporus mushrooms in this study were closer to the lower range of results (mean 36 ± 14 mg kg −1 dw, and total range from 13 to 75 mg kg −1 dw; n = 72 fruit bodies) and 65 ± 9 mg kg −1 dw (n = 15) published for the white strain of button mushroom available from retail outlets in Poland, during 1989-2015, respectively (Falandysz et al 1993Pankavec et al 2019;Rzymski et al 2017), and similarly, for the Australian cultivated white button mushrooms from two producers (range of the means from 35 ± 2 to 61 ± 2 mg kg −1 dw in 6 pools of an unknown number of fruiting bodies) (Koyyalamudi et al 2013). The authors Falandysz et al (1993), Muszyńska et al (2017), Rzymski et al (2017) and Vetter et al (2005) reviewed data on Cu in A. bisporus and presented values in the range from 25 to 125 mg kg −1 dw, from 3 to 65 mg kg −1 dw and from 6.8 to 61 mg kg −1 dw, respectively (no information was provided on the analytical quality of compiled data and sample size information was not included).…”
Section: Copper Manganese and Zincsupporting
confidence: 89%
“…Mushrooms preparation techniques, e.g., blanching, boiling, parboiling, pickling, braising, stewing, grilling, frying, soaking (macerating), and also industrial conserving (pickling and canning), have an effect on the content of mineral constituents in processed products (Beresford et al 2001 ; Drewnowska et al 2017 ; Falandysz et al 2020a , b ; Pankavec et al 2019 ; Skibniewska and Smoczyński 1999 ; Steinhauser and Steinhauser 2016 ; Stijve 1994 ). Daillant et al noted that routine culinary practices using a variety of different treatments were only partly successful in decreasing 137 Cs contents in potential mushroom meals (Daillant et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adequate potassium daily intake for adults has been set for 4700 mg (NIH 2019 ), and a serving composed of 100 g stir-fried (whole weight) mushroom meals containing between 380 and 770 mg of K (mean 500 ± 130 mg; Table 2 ) and assuming that absorption rate by body is 85 to 90% classifies the mushroom meals in this study among a good potential dietary source of potassium. Mushrooms that are conserved are much poorer source of potassium (Pankavec et al 2019 ) than the stir-fried products.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty years before the nuclear accident at Chernobyl, mushrooms were already recognized as a possible source of 137 Cs contamination (coming from the nuclear weapon explosions) for humans (Kiefer and Maushart 1965 ). However it has also been observed that intake through this pathway could be reduced by cooking processes, e.g., blanching or boiling with excess of water, can decrease the mushroom content of artificial 137 Cs and the alkali metals, e.g., Li and Cs, which leak into the discarded water phase (Consiglio et al 1990 ; Daillant et al 2013 ; Pankavec et al 2019 ; Skibniewska and Smoczyński 1999 ; Stijve 1994 ).…”
Section: Introductionmentioning
confidence: 99%